In-process thermal damage detection in grinding with monitoring via Internet - Dotto, Fábio R.L. [UNESP]; Aguiar, Paulo R. [UNESP]; Bianchi, Eduardo C. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2002)
This work aims the development of a dedicated system for detection of burning in surface grinding process, where the process will constantly be monitored through the acoustic emission and electric power of the induction motor drive. Acquired by an analog-digital converter, algorithms process the signals and a control signal is generated to inform the operator or interrupt the process in case of burning occurrence. Moreover, the system makes possible the process monitoring via Internet. Additionally, a comparative study between parameters DPO and FKS is carried through. In the experimental work one type of. steel (ABNT-1020 annealed) and one type of grinding wheel referred to as TARGA, model ART 3TG80.3 NVHB, were employed.
Keywords: Acoustic emissions; Algorithms; Analog to digital conversion; Electric power utilization; Induction motors; Internet; Thermal effects; Metal mechanics industry; Thermal damage; Grinding (machining)